School Inspection in Tanzania as a Motor for Education Quality: Challenges and Possible Way Forward - Kambuga, Yusuph; Dadi, Habibu (Review of Knowledge Economy, 2015)
The quest for having quality education has always been the Tanzania dream and can be traced even soon after independence. After independence 1961, Tanzania passed different laws and a number of Acts as to regulate the education in the country, among the laws and Acts passed by the government, the most important one is education Act No 25 of 1978 which led to the establishment of School Inspectorate. Since then, the school inspection was recognized as the legal instrument to be undertaken by selecting education specialists as a strategy to monitor education quality in the country. The purpose of this paper is to illuminate the Tanzanian experience on school inspection as an instrument for quality assurances in the overall process of teaching and learning. Efforts have been made to discuss how effective school inspectorate is supposed to be in order to improve the standards and quality of teaching and learning process in the educational institutions.